API-related developer information needs in Stack Overflow - LIU, Mingwei (Institutional Knowledge at Singapore Management University, 2022)
Stack Overflow (SO) provides informal documentation for APIs in response to questions that express API related developer needs. Navigating the information available on SO and getting information related to a particular API and need is challenging due to the vast amount of questions and answers and the tag-driven structure of SO. In this paper we focus on identifying and classifying fine-grained developer needs expressed in sentences of API-related SO questions, as well as the specific information types used to express such needs, and the different roles APIs play in these questions and their answers. We derive a taxonomy, complementing existing ones, through an empirical study of 266 SO posts. We then develop and evaluate an approach for the automated identification of the fine-grained developer needs in SO threads, which takes a thread as input and outputs the corresponding developer needs, the types of information expressing them, and the roles of API elements relevant to the needs. To show a practical application of our taxonomy, we introduce and evaluate an approach for the automated retrieval of SO questions, based on these developer needs.